Effect of host microenvironment and bacterial lifestyles on antimicrobial sensitivity and implications for susceptibility testing - Ramon Garcia-Maset; Victoria Chu; Nicholas Yuen; Dalia Blumgart; Jenny Yoon; Benjamin O. Murray; Amelia A. Joseph; Jennifer L. Rohn (npj Antimicrobials and Resistance)
Abstract Bacterial infections remain a major global health issue, with antimicrobial resistance (AMR) worsening the crisis. However, treatment failure can occur even when bacteria show antibiotic susceptibility in diagnostic tests. We explore factors such as phenotypic resilience, bacterial lifestyles such as biofilms, and differences between laboratory tests and real infection sites, highlighting the need for improved platforms to better predict treatment outcomes, and reviewing emerging technologies aimed at improving susceptibility testing.